2022
DOI: 10.2196/41415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Implementation of Mobile Health to Improve the Uptake of Hydroxyurea in Patients With Sickle Cell Disease: Mixed Methods Study

Abstract: Background Hydroxyurea therapy is effective for reducing complications related to sickle cell disease (SCD) and is recommended by National Health Lung and Blood Institute care guidelines. However, hydroxyurea is underutilized, and adherence is suboptimal. We wanted to test a multilevel mobile health (mHealth) intervention to increase hydroxyurea adherence among patients and improve prescribing among providers in a multicenter clinical trial. In the first 2 study sites, participants were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Due to the COVID-19 pandemic restrictions for in-person research activities, virtual enrollment was initiated. The sites most affected by clinic shutdowns were the first 2 sites, as previously reported [ 9 ]. Although clinic lockdowns were no longer in effect when the remaining 5 sites opened enrollment, these sites were also affected by long-term changes related to the pandemic (eg, staff resignation, remote working).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Due to the COVID-19 pandemic restrictions for in-person research activities, virtual enrollment was initiated. The sites most affected by clinic shutdowns were the first 2 sites, as previously reported [ 9 ]. Although clinic lockdowns were no longer in effect when the remaining 5 sites opened enrollment, these sites were also affected by long-term changes related to the pandemic (eg, staff resignation, remote working).…”
Section: Resultsmentioning
confidence: 66%
“…In March 2020, only 4 months after the study began recruiting providers and 2 months after the initiation of patient recruitment, the global COVID-19 pandemic emerged in the United States. In response to the pandemic, institutions were forced to modify clinical and research procedures by temporarily suspending all nonessential in-person contact [ 9 ]. This rapid procedural change directly impacted all in-person research activities in meSH, which was initially designed to conduct all recruitment in person.…”
Section: Introductionmentioning
confidence: 99%
“…Low participant numbers needing acute healthcare intervention during the trial precluded meaningful comparison of clinical effects by group. While we were unable to assess pandemic‐related effects on HU adherence, a separate US‐based SCD trial demonstrated reduced HU adherence during the public health emergency 38 . Nationally, trial interruption in non‐COVID‐19 studies substantially increased during that period 39 …”
Section: Discussionmentioning
confidence: 91%
“…While we were unable to assess pandemic-related effects on HU adherence, a separate US-based SCD trial demonstrated reduced HU adherence during the public health emergency. 38 Nationally, trial interruption in non-COVID-19 studies substantially increased during that period. 39 Results from the intervention group suggest a positive impact intervention expressed positive perspectives on the CHW-led intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low adherence to hydroxyurea as seen in this study, new strategies are needed to achieve full drug benefits. Novel interventions using mobile health are being investigated and may represent a self‐management tool to support medication adherence 50–52 . Finally, our data highlights the need to investigate newer SCA‐approved therapies (e.g., voxelotor, crizanlizumab) and other therapeutic modalities such as curative treatments, that mitigate microvascular ischemic and endothelial injury, and explore their role in potentially preventing the ventricular remodeling that drives the cardiac injury seen in SCA.…”
Section: Discussionmentioning
confidence: 98%